Not Just Anywhere, Anywhen: Mapping Change through Studio Work - Tassoni, John Paul and Lewiecki-Wilson, Cynthia (Journal of Basic Writing, 2005)
In this autoethnographic, institutional narrative, we describe the evolution of a Studio program at an open-access, regional campus of a state university. The Studio, first conceptualized by Grego and Thompson, is a one-credit writing workshop taken by students concurrently enrolled in a composition course. Developing this program necessitated incursion into an institutional landscape that we learned was not transparent, unclaimed, or uncontested. In remaking that landscape, we came to understand the crucial roles of space and place, power and colonization, in institutional change and in the teaching of writing. Institutional spaces are never transparent, unclaimed, or uncontested; thus remaking an institutional landscape involves issues of power and colonization. Postcolonial theories helped us think about the shifting and asymmetrical relations of power embroiling us as we struggled to bring about change in our campus's approach to at-risk students. We argue that the contradictions and confusions students experience in the university embody the work in Studio, and that these contradictions must not be smoothed out in any narrative we write or theorizing we attempt.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MzQ0MzgxMQ